FROM MADHAB TO SOCIAL DOGMA: THE TABLIGHIJEMAATâS FLUIDITY OF TEACHINGS AND THE INTEGRATION OF UMMAH - Ilyasin, Mukhammad (LENTERA: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Tablighi Jamaat is one of the largest Muslim organization in the world. Despite lacking formal form of organization like other Islamic organization in general, the members of the Tablighi Jamaat is well known for their loyalty and discipline in implementing the principles of the organization, especially regarding the organizationsâ guidelines on conducting daâwa to Muslims with different religious background such as madhab affiliation. This paper, therefore, aims at explaining the strategy of performing daâwa applied by the Tablighi Jamaat in plural social settings. Findings suggest that the Tablighi Jamaat utilized the notion of equality as its most important principle of daâwa. The idea of equality is actualized through several mechanism like madhab fluidation, desacralization of madhab and demadhabization. In this context, every member of the Tablighi Jamaat has the same opportunity to be daâI (preacher) as well as to be madâu (audience).Keywords: Tablighi Jamaat, Strategy of Daâwa, Desacralization, Demadhabization and Madhab Fluidation.